Progress Towards the Syntheses of Ortho-Farnesylated Phenolic Natural Products - Lach, Elizabeth (My University, 2024)
Natural products have been an important part of medicine for centuries, starting from traditional medicines and remaining significant in drug discovery today. This thesis will focus on ortho-farnesylated phenolic natural products. Chapter 1 is a comprehensive review of the literature concerning ortho-farnesylated phenolic natural products, their natural occurrence, biosynthesis, bioactive properties, and methodologies toward their de novo synthesis. Chapter 2 showcases the first total synthesis of isoindolinone natural product chartarutine B which was isolated from the fungi Stachybotrys chartarum and shown to have moderate anti-HIV bioactivity. The four-step synthetic route features the use of a cobalt-catalyzed C(sp2)-H carbonylation and novel regioselective alumina-templated phenol ortho-farnesylation developed by the Magolan group. Chapter 3 focuses on the progress towards the first total syntheses of highly substituted phenolic natural products tuaimenal A and H, which were isolated from the deep-sea sponge Duva florida. Both compounds are modestly cytotoxic to two cervical cancer cell lines (EC50 46 μM, 23 μM; CaSki). Additionally, tuaimenal A is a viral protease inhibitor (EC50 21 μM; SARS-CoV-2 3CLpro). The synthetic route includes another application of the Magolan group ortho-farnesylation chemistry. Chapter 4 describes the synthesis of a library of structural analogues of lead compound NP-BTA, a potent inhibitor of Gln4 in the fungal pathogen Candida albicans that was conducted in collaboration with the laboratory of Prof. Leah Cowen at the University of Toronto. In this chapter, the structure-activity relationship study is summarized, and all details of the synthetic chemistry involved in this collaborative project are reported.
Keywords: Total Synthesis; Organic Synthesis; Medicinal Chemistry; Natural Products; Chartarutine; Tuaimenal